Advantages of Using Lotteries to Select Participants for High‐Demand Covid‐19 Treatment Trials. Issue 4 (22nd June 2020) - Iyer, Alexander A.; Hendriks, Saskia; Rid, Annette
ABSTRACT: As hospitals have experienced a surge of Covid‐19 patients, investigators of Covid‐19 treatment trials face a difficult problem: when an institution has more eligible and interested patients than trial slots, who should be enrolled? Defining a clear strategy for selecting participants for "high‐demand" Covid‐19 treatment trials is important to avoid ad hoc and potentially biased decision‐making by local investigators, which could inadvertently compromise a trial's social value, participants' interests, or fairness. In this article, we propose a set of ethical criteria for evaluating participant‐selection strategies for such trials. We argue that the pandemic context—in particular, great urgency to develop safe and effective treatments, uncertainty surrounding Covid‐19, and strain on the health care system that limits the time and effort available for trial enrollment—favors participant‐selection strategies that optimize the ease of enrollment and, ideally, social value. A lottery and, where possible, a weighted lottery have important advantages in these respects.